Association of Body Mass Index With Disability in Activities of Daily Living Among Chinese Adults 80 Years of Age or Older - Lv, Yue-Bin (JAMA Netw Open, 2018)
IMPORTANCE: Body mass index (BMI) shows a U-shaped association with impaired physical functioning among adults; the association is reduced or eliminated with aging. OBJECTIVE: To examine whether BMI is associated with subsequent disability in activities of daily living (ADL) in Chinese adults age 80 years or older. DESIGN, SETTING, AND PARTICIPANTS: Data were obtained on 16 022 adults age 80 years or older who were able to perform ADL independently at baseline from the Chinese Longitudinal Healthy Longevity Study, a community-based prospective cohort study conducted in 23 provinces of China. The study was initiated in 1998, with follow-up and recruitment of new participants in 2000, 2002, 2005, 2008, 2011, and 2014. MAIN OUTCOMES AND MEASURES: Disability in ADL was defined as dependence in eating, toileting, bathing, dressing, indoor activities, and/or continence. RESULTS: Among the 16 022 participants, 45.2% were men and 54.8% were women, with a mean (SD) age of 92.2 (7.2) years and a mean (SD) BMI (calculated as weight in kilograms divided by height in meters squared) of 19.3 (3.8). During 70 606 person-years of follow-up, 8113 participants with disability in ADL were identified. Cox proportional hazards regression models with penalized splines showed that BMI was linearly associated with disability in ADL: each 1-kg/m(2) increase in BMI corresponded to a 4.5% decrease in the risk of disability in ADL. In comparison with individuals in the fourth quintile for BMI, the adjusted hazard ratio for disability in ADL was 1.38 (95% CI, 1.29-1.48) in the first quintile, 1.37 (95% CI, 1.28-1.47) in the second quintile, 1.11 (95% CI, 1.04-1.19) in the third quintile, and 0.85 (95% CI, 0.79-0.91) in the fifth quintile (P < .001 for trend). When BMI was categorized by Chinese guidelines, the underweight group (BMI <18.5) showed significantly increased risk of disability in ADL (hazard ratio, 1.34; 95% CI, 1.28-1.41) and the overweight or obese group (BMI ≥24.0) showed significantly decreased risk of disability in ADL (hazard ratio, 0.84; 95% CI, 0.78-0.91) compared with the normal weight group (BMI 18.5 to <24.0) (P < .001 for trend). CONCLUSIONS AND RELEVANCE: Higher BMI was associated with a lower risk of disability in ADL among Chinese adults age 80 years or older, which suggests that current recommendations for BMI may need to be revisited. More attention should be paid on underweight, rather than overweight or obesity, for the prevention of disability in ADL after age 80 years.